The mediating role of proactive coping in the relationships between stress mindset, challenge appraisal tendencies, and psychological wellbeing - Mansell, Paul C.; Turner, Martin J. (Frontiers in Psychology, 2023)
Objective Stress is ubiquitous and how individuals view the nature of stress can influence psychological wellbeing. The present study aimed to investigate the mediating role of proactive coping on the relationships between stress mindset and challenge appraisal tendencies and examine how this in turn related to psychological wellbeing. A secondary aim was to investigate if there were any differences in stress mindset between athletes and non-athletes. It was hypothesised that stress mindset would be indirectly positively associated with challenge appraisal tendencies through proactive coping, that a challenge appraisal tendency would positively relate to vitality, and that vitality would negatively relate to depressive symptoms. It was also hypothesised that athletes would possess more facilitative views of stress compared with non-athletes. Methods Two hundred and seven individuals (n = 101 athletes, n = 106 non-athletes, Mage = 22.76 years, SD = 4.94) completed an online questionnaire pack assessing stress mindset, proactive coping, challenge appraisal tendencies, vitality, and depressive symptoms. Results Using path analysis, the hypothesised model demonstrated a good fit to the data and the positive relationship between stress mindset and challenge appraisal tendencies was mediated by proactive coping. Challenge appraisal tendencies were positively associated with vitality, which was negatively associated with depressive symptoms. Athletes reported a significantly greater ‘stress-is-enhancing’ mindset, greater vitality, and fewer depressive symptoms than non-athletes. Conclusions Findings offer support for the role that stress mindset has in potentially influencing psychological wellbeing and offer the novel suggestion that this mechanism may operate through proactive coping and challenge appraisal tendencies.